APLIKASI NUTRISI ABC MIX DAN GA3 PADA SISTEM TANAM SOILLESS PADI MERAH - Annisa' Dyah amiril laksita; Tirto Wahyu Widodo; Ilham Muhklisin; Mahindra Dewi Nur Aisyah; Ahya Ibadina Syahida; Epi Nindia Pustika Ningtias (Politeknik Negeri Lampung., 2026)
The use of AB mix as a nutrient in soilless rice cultivation actually prolongs the vegetative phase which results in late flowering and suboptimal grain filling. This study aims to examine the effect of ABC Mix (AB Mix + silica) and gibberellin nutrients on flowering age, growth, and yield of red rice in a soilless cultivation system. This experiment was designed using a split plot design, where ABC mix nutrients were the main plot while gibberellins were the subplots and replicated three times. The concentration of ABC Mix nutrients consisted of 4 levels, namely 750-800 ppm, 1000-1050 ppm, 1250-1300 ppm, and 1500-1550 ppm, while the concentration of gibberellins consisted of 2 levels, namely 0 ppm (control) and 200 ppm. The results showed that there was a significant interaction between the ABC Mix 750-800 ppm and GA3 200 ppm treatments on plant height (192.0 cm). The single treatment of GA3 200 ppm showed a significant effect on plant height (192.0 cm), while the ABC Mix treatment of 750-800 ppm showed a significant effect on the total number of tillers (60.03 stems), the number of productive tillers (23.03 stems), panicle length (55.42 cm), and plant height (192.0 cm). However, the addition of silica to the AB Mix (ABC Mix) and the applied GA3 was not able to accelerate the flowering phase, where the flowering time was still above 80 days after planting. This was suspected to be due to the inappropriate timing of GA3 application, while the activation of the flower meristem gene takes about 5 days after GA3 application. The inaccuracy in the timing of GA3 application actually resulted in the growth of gigas plants (twice as much as normal plants) and a low number of productive tillers (±38% of the total number of tillers).